Card Sorting as Collaborative Method for User-Driven Information Organizing on a Website: Recommendations for Running Collaborative Group Card Sorts in Practice - Bjerre, Maria Friis (Communication & Language at Work, 2015)
Card sorting is an easy-to-use, quick, inexpensive, yet powerful usability method for information organizing on a website as it generates usable input directly from end-users as to how they would expect to find information on a website. When run collaboratively in groups, the discussion between the users about the content of the cards and their relatedness provides valuable insight into the users’ mental models. Focusing on epistemic asymmetry in the group discussion, this article highlights important issues which may affect the outcome of group card sorting. It is demonstrated that group card sorting demands great attention from the test manager in relation to the composition of the group, i.e. the number of users per group and the users’ educational level and formal organizational positions, in order to ensure a result that is representative of the group as a whole.